UTILIZATION OF DIGITAL TECHNOLOGY TO PRESERVE CHINESE WALL PAINTINGS AS CULTURAL HERITAGE - Elizabeth Susanti GUNAWAN; Miki TJANDRA (Geo Journal of Tourism and Geosites)
According to historical records of Admiral Chengho's arrival, Jamblang Indonesia has existed since the fifteenth century. The temple in Jamblang has a very valuable historical heritage. Classic Chinese stories are displayed in paintings t hat cover every wall of the temple structure. However, the condition of the paintings is not good due to damage from incense smoke, faded colors, and cracked and moldy walls. The Chinese paintings on the temple walls are evidence of traces of Chinese culture which has a long history. The paintings were left unattended due to a lack of understanding and care, increasing the possibility that they would become increasingly blurry or perhaps disappear under the cover of incense smoke. This research aims to utilize digital technology as a solution for documenting these paintings to preserve and revitalize them. The methods used are documentation and digital image processing. Documentation is carried out by taking a photo of each image at eye level to minimize distortion. The difficulties faced were a narrow place to take photos with minimal distance, paintings that were blocked by several temple artifacts, lighting in the room that was very dark, and image tracing that was almost faded. The photos obtained are collected and processed using digital technology. Each part of the wall painting is documented, corrected and traced to obtain a collection of paintings in digital form that can be applied to various types of media. This research produces an image-processing framework for digitizing documentation to preserve cultural heritage. The results show traces of a high-value culture that has existed for a long time.